CARACTERIZAÇÃO DAS MULHERES IDOSAS QUE NÃO PARTICIPAM DE GRUPOS DE CONVIVÊNCIA - Beienke, Flavio; Roncato, Claudia A.; Kitzmann, Francine; Stumm, Eniva M. F.; Leite, Marinês T.; Hildebrandt, Leila M.; Kirchner, Rosane M.; Rieth, Giovani H. (Salão do Conhecimento, 2013)
Resumo